Correlating the chemical structure and charge transport ability of dibenzofulvene-based hole transporting materials for stable perovskite solar cells. Issue 15 (23rd March 2022) - Leoncini, M.; Capodilupo, A.-L.; Altamura, D.; Giannini, C.; Accorsi, G.; Fabiano, E.; Rizzo, A.; Gigli, G.; Gambino, S.
Abstract : By modifying the size and shape of the molecules, we managed to tune the hole mobility of our HTMs up to three orders of magnitude. Our best HTM led to a solar cell lifetime that is tripled compared to that based on spiro-OMeTAD. Abstract : Hole transporting materials (HTMs) play a crucial role in developing highly efficient and stable perovskite solar cells (PSCs). Their function is to extract and transport hole carriers, but at the same time protect the perovskite layer from environmental conditions (n–i–p PSCs). Therefore, there is a need to develop new HTMs to better balance all of the above functions and performances to make efficient, stable and possibly low-cost PSCs. To address these issues, we studied the structure–performance relationship of a series of recently synthesized star-shaped molecules characterized by a dibenzofulvene core, a thiophene ring and three arylamino moieties, but varying in size (thiophene number) and shape (anchoring position of arylamines to the core). By the interplay between size and shape, we managed to tune the hole mobility by up to three orders of magnitude, and our best compound (T2N3 ) showed a zero-field mobility value (3 × 10 −5 cm 2 V −1 s −1 ) comparable to that of spiro-OMeTAD. Not only the mobility but also the main charge transport parameters were analyzed from the temperature-dependent space charge limited current characteristics. Usually, this analysis relies on simplified empirical equations but in the present case they were extracted by solving drift-diffusion equations. More importantly, we parametrized the field and temperature mobility dependence by simulating hopping transport via sites located on either regular grids or randomly distributed ones. The resulting transport parameters were correlated with the structure and morphology of the materials. The relatively good mobility of T2N3 combined with its good film-forming properties, which translates into good interaction with perovskites (efficient hole extraction), led to PSC efficiencies comparable to those of spiro-OMeTAD. Moreover, the laboratory synthesis of T2N3 was simpler and cheaper than that of commercially available spiro-OMeTAD. Importantly, non-encapsulated solar cells employing T2N3 showed an 80% efficiency lifetime of 2400 h (100 days), which is triple that of spiro-OMeTAD based ones. Thus, we propose T2N3 as a promising alternative to the expensive and poorly stable spiro-OMeTAD.